1993
DOI: 10.1007/bf00028976
|View full text |Cite
|
Sign up to set email alerts
|

Destabilization of pea lectin by substitution of a single amino acid in a surface loop

Abstract: Legume lectins are considered to be antinutritional factors (ANF) in the animal feeding industry. Inactivation of ANF is an important element in processing of food. In our study on the stability of Pisum sativum L. lectin (PSL), a conserved hydrophobic amino acid (Val103) in a surface loop was replaced with alanine. The mutant lectin, PSL V103A, showed a decrease in unfolding temperature (Tm) by some 10 degrees C in comparison with wild-type (wt) PSL, and the denaturation energy (delta H) is only about 55% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 37 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…Loops are known to affect the stability of a protein fold (Gekko et al, 1993;Hoedemaeker et al, 1993;Dion-Schultz & Howell, 1997;Fetrow et al, 1997). This is illustrated notably by circularly permuted proteins (Garrett et al, 1996;Uversky et al, 1996) where natural turns and artificial linkers can make the difference between a well-folded protein and a molten globule.…”
Section: Discussionmentioning
confidence: 99%
“…Loops are known to affect the stability of a protein fold (Gekko et al, 1993;Hoedemaeker et al, 1993;Dion-Schultz & Howell, 1997;Fetrow et al, 1997). This is illustrated notably by circularly permuted proteins (Garrett et al, 1996;Uversky et al, 1996) where natural turns and artificial linkers can make the difference between a well-folded protein and a molten globule.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, fl-loops have always been found at the protein surface and their lack of regular hydrogen bonding patterns suggests that these structures do not play a role in protein structure and stability, however, single and multiple mutations in some fl-loops can have drastic effects on overall protein stability. A single change from a valine to an alanme in an fl-loop in pea lectin caused a 100 decrease in the melting temperature of the protein (42). The researchers suggest this destabilization is caused by a loss of hydrophobic contacts between the loop and the protein.…”
Section: What Do Fl-loops Do In Proteins? a Role In Protein Stabilitymentioning
confidence: 99%
“…Using this approach, we have shown that mutants of PHA containing three and four methionine residues stably accumulate in the vacuoles of tissue-cultured cells and the protein storage vacuoles of seeds. Although minor modifications of seed storage proteins have been shown not to affect transport and targeting, one must be cautious with this approach since a report by Hoedemaeker et al (1993) showed that pea lectin was thermally destabilized by the modification of a single amino acid. Recently, Dyer et al (1993) proposed a similar method to replace individual amino acids with methionine residues for the seed storage protein phaseolin although the replacements were based on conserved hydrophobic residues, not conserved methionine residues.…”
Section: Discussionmentioning
confidence: 99%